On the issue of legal personality of participants in public and legal relationships in the sphere of providing administrative services: defi nition of approach (Journal of actual problems of jurisprudence, 2019)
The article is devoted to the justifi cation of a scientifi c approach to the characterization of administrative legalpersonality of participants in public and legal relations in the sphere of providing administrative services. Thereis justifi ed the conclusion that the subject of law in sphere of providing administrative services should be viewedas legal abstraction that acquires material character in specifi c legal relationships – as for providing administrativeservices. Such materialization consists of a set of rights, obligations and legal capacity of participants in public andlegal relationships in the sphere of providing administrative services. There is proved that the participants in such legalrelationship are characterized by general and specialized legal personality and, accordingly – by combination of generaland special rights, obligations and legal possibilities.Key words: administrative services, administrative legal personality, rights, obligations, legal possibilities.